The Mediating Role of Organizational Commitment in the Effect of Work Ethics and Employee Engagement on Employee Performance (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the mediating role of organizational commitment in the relationship between work ethics, work engagement, and employee performance. The research was conducted at the Central Java Regional Office of the Animal, Fish, and Plant Quarantine Agency, involving a population of 256 employees. A purposive sampling technique was applied, resulting in 156 valid respondents. Data were collected through structured questionnaires and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach with the SmartPLS 3 software. The results of the analysis indicate that work ethics and work engagement have a positive and significant influence on organizational commitment. In addition, work ethics, work engagement, and organizational commitment are proven to have a positive and significant effect on employee performance. Further mediation analysis using the Sobel test reveals that organizational commitment plays a significant mediating role in strengthening the effect of work ethics and work engagement on employee performance. These findings highlight the importance of fostering ethical behavior and employee engagement to enhance organizational commitment, which in turn contributes to improved employee performance and overall organizational effectiveness.